Artikel Review: Produksi Bioetanol dari Limbah Biomassa dengan Fermentasi Menggunakan Bantuan Yeast - Pratiwi, Wiwik; Ni Made, Suaniti (Program Studi Teknik Kimia Universitas Jember, 2023)
Bioethanol is an ethanol compound made from biomass containing starch, sugar and cellulose. The most common production of bioethanol uses hydrolysis and fermentation methods. The following article aims to compare the levels of bioethanol produced from various types of biomass using various methods. The method used can be in the form of variations in the concentration of acids and bases used in hydrolysis, fermentation time and the mass of yeast used. The results of the review of the article found that the highest levels of bioethanol were obtained from bioethanol made from banana peels by hydrolysis and fermentation methods. The glucose level produced was 3.13% and the bioethanol content obtained was 13.54% with a fermentation time of 144 hours. Keywords: Bioethanol, Fermentation, Hydrolysis, Yeast, Glucose